Inter-rater agreement, sensitivity, and specificity of the prone hip extension test and active straight leg raise test - Bruno, Paul A (BioMed Central, 2014)
BACKGROUND: Two clinical tests used to assess for neuromuscular control deficits in low back pain (LBP) patients are the prone hip extension (PHE) test and active straight leg raise (ASLR) test. For these tests, it has been suggested examiners classify patients as “positive” or “negative” based on the presence or absence (respectively) of specific “abnormal” lumbopelvic motion patterns. The inter-rater agreement of such a classification scheme has been reported for the PHE test, but not for the ASLR test. In addition, the sensitivity and specificity of such classification schemes have not been reported for either test. The primary objectives of the current study were to investigate: 1) the inter-rater agreement of the examiner-reported classification schemes for these two tests, and 2) the sensitivity and specificity of the classification schemes. METHODS: Thirty participants with LBP and 40 asymptomatic controls took part in this cross-sectional observational study. Participants performed 3–4 repetitions of each test whilst two examiners classified them as “positive” or “negative” based on the presence or absence (respectively) of specific “abnormal” lumbopelvic motion patterns. The inter-rater agreement (Kappa statistic), sensitivity (LBP patients), and specificity (controls) were calculated for each test. RESULTS: Both tests demonstrated substantial inter-rater agreement (PHE test: Kappa = 0.76, 95% CI = 0.57-0.95, p < 0.001; ASLR test: Kappa = 0.76, 95% CI = 0.57-0.96, p < 0.001). For the PHE test, the sensitivity was 0.18-0.27 and the specificity was 0.63-0.78; the odds ratio (OR) of “positive” classifications in the LBP group was 1.25 (95% CI = 0.58-2.72; Examiner 1) and 1.27 (95% CI = 0.52-3.12; Examiner 2). For the ASLR test, the sensitivity was 0.20-0.25 and the specificity was 0.84-0.86; the OR of “positive” classifications in the LBP group was 1.72 (95% CI = 0.75-3.95; Examiner 1) and 1.57 (95% CI = 0.64-3.85; Examiner 2). CONCLUSION: Classification schemes for the PHE test and ASLR test based on the presence or absence of specific “abnormal” lumbopelvic motion patterns demonstrated substantial inter-rater agreement. However, additional investigation is required to further comment on the clinical usefulness of the motion patterns demonstrated by LBP patients during these tests as a diagnostic tool or treatment outcome.